Propuesta metodológica para determinar el nivel de trabajo decente en la población económicamente activa (PEA) ocupada de la provincia de Trujillo - Bocanegra Andrade, Elisa Noelia (2016)
The aim of this work is to introduce a methodology for measuring the level of Decent Work in the Province of Trujillo, this is Decent Work Index from the workplace, in order to do that, the Economically Active Population Occupied within the city was evaluated based on a set of indicators, in which ENAHO 2014 has been the main source of information. The results suggest, according to the distribution of employed persons in the proposed Decent Work Index, that 379 thousand and 349 people 15.9% belonged to level 1 scale, that is to say, met all the conditions and requirements worthy according to decent work as defined in this study. On the other hand, 7, 1% was located at level 5, did not meet any of the 5 indicators and ultimately did not have a decent job. Also that 33,3% were at level 4 and 5, which is to say than a third of the population it just met at least one of the supplementary conditions of decent work. The picture shows a positive trend on the improving the quality of work, also shows decent work deficit, so it is necessary to adjust the compliance of relevant indicators.